Novel high-water-resistance cement capillary crystalline mortar and preparation method thereof
By using cement-based permeable crystalline waterproof additives in concrete, the internal structure of insoluble crystal filled concrete is generated, which solves the aging and leakage problems of existing waterproof materials and achieves a concrete mortar with high water resistance and durability.
Patent Information
- Application Number
- CN202510011711.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-04
- Publication Date
- 2025-03-28
AI Technical Summary
Existing waterproof materials are prone to aging and cracking during long-term use, resulting in leakage and cracking problems in concrete structures, reducing the safety and durability of the structure.
Cement-based permeable crystalline waterproof additive is used to generate insoluble crystals by reacting with unhydrated substances in the concrete, filling the micropores and capillary channels of the concrete to improve the density and waterproof performance of the mortar.
It achieves significantly improving its impermeability and durability without reducing the strength of concrete, and enhances the safety of concrete structure.
Smart Images

Figure CN119707406A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, in particular to a novel high-water-resistant mortar, and in particular to the technical field of a novel high-water-resistant cement penetrating crystallization mortar and a preparation method thereof. Technical Background
[0002] With the acceleration of global urbanization and industrialization, and the continuous improvement of infrastructure construction, higher standards have been set for the safety and durability of structures. As the most commonly used structural material in construction, the performance of concrete is crucial to meeting these high standards. However, concrete is a porous and non-uniform material, and leakage problems often occur during use. Leakage problems not only reduce the durability of structural materials, but also shorten their expected service life. Waterproofing is of great significance to the quality of concrete structures. At present, waterproof materials mainly include waterproof membranes, waterproof coatings, and rigid waterproof materials. Although these traditional waterproof materials can protect concrete structures from moisture erosion in the early stage of use, these waterproof layers often gradually degrade due to aging, cracking, and other problems during long-term use, resulting in serious leakage and cracking in concrete structures, greatly reducing the safety and durability of the structure. Therefore, exploring and developing new waterproof materials to overcome the limitations of traditional materials has become an important issue that needs to be urgently addressed in the field of building materials.
[0003] Prior art JPH0288451A discloses a waterproof cement admixture for improving the waterproofing effect of concrete, etc., obtained by mixing a calcium sulfoaluminate complex, which contains an active siliceous material.
[0004] CN1587173A discloses a cement-based permeable crystallization waterproof material, the active component of which mainly includes a combination of one or two or three of 0.2-0.6% sodium fluoride, 0.3-0.5% sodium aluminate and 0.2-0.6% sodium sulfate. The material has the function of improving the water resistance and impermeability of concrete.
[0005] In recent years, cement-based permeable crystalline waterproofing material (CCCW) has attracted widespread attention as a new type of waterproofing material. It has the advantages of good compatibility with concrete, environmental protection, long-term waterproofing and convenient construction. Generally speaking, CCCW is used to coat the surface of concrete. In this case, CCCW has little effect on its mechanical properties. Cappellesso (VGCappellesso, NDS Petry, DCCD Molin, AB Masuero, Use of crystalline waterproofing to reduce capillary porosity in concrete, J. Build. Rehabil. 1(1) (2016) 1–12, https: / / doi.org / 10.1007 / s41024-016-0012-7) and other studies found that compared with ordinary concrete, the compressive strength of CCCW-coated concrete increased from 41.55MPa to 42.86MPa, an increase of 3%. In recent years, some studies have also directly added CCCW to concrete. For example, Azarsa (P.Azarsa, R.Gupta, A.Biparva, Assessment of self-healing and durability parameters of concretes incorporating crystalline admixtures and Portland Limestone, Cement. Cem.Concrete. Comp. 99 (2019) 1731, https: / / doi.org / 10.1016 / j.cemconcomp.2019.02.017.) et al. found that the water penetration height of concrete with CCCW was nearly 50% lower than that of ordinary concrete. This is because CCCW reacts with concrete to form insoluble crystals, which fill the pores inside the concrete and make the concrete more compact. It can be seen that CCCW has a positive effect on the durability of concrete. However, at this time, CCCW has a significant effect on the mechanical properties of concrete.Calvo et al. (JLGCalvo, MSMoreno, P.Carballosa, F. Pedrosa, F.Tavares, Improvement of the concrete permeability by using hydrophilic blended additive, Materials 1 (2019) 2384, https: / / doi.org / 10.3390 / ma12152384.) found that adding CCCW can improve the compressive strength of concrete, with the compressive strength increasing by 19.5%. Zheng et al. (K. Zheng, X. Yang, R. Chen, R. Xu, Application of acapillary crystalline material to enhance cement grout for sealing tunnelleakage, Construct. Build. Mater. 214 (2019) 497–505, https: / / doi.org / 10.1016 / j.conbuildmat.2019.04.095.) studied cement gravel concrete with CCCW added. When the concentration of CCCW increased from 0.8% to 1.2%, the strength increased significantly, from 4.9MPa to 5.8MPa. However, when the concentration is greater than 1.2%, the strength of the concrete decreases. This is because with the increase in the amount of CCCW, CCCW reacts with unhydrated substances to generate many crystals, but when the amount is excessive, too many crystals will be generated. The excessive crystal generation puts pressure on the inside of the concrete, causing obvious cracks inside the concrete and reducing the strength of the concrete. The above studies have proved that the addition of CCCW can not only improve the durability of concrete, but also have a positive or negative impact on the strength of concrete.
[0006] The applicant has made great efforts to discover a cement-based penetrating crystalline waterproofing agent to modify mortar, and obtained a mortar and a preparation method that improve the cement penetration ability without significantly reducing or reducing the strength.
[0007] Therefore, the present invention plans to study the influence of CCCW dosage and water-cement ratio on the tensile strength, compressive strength and impermeability of mortar specimens, so as to obtain a new type of highly water-resistant cement penetration crystallization mortar with excellent mechanical properties and a preparation method thereof, which provides a theoretical basis for the subsequent related research and promotion of CCCW materials in concrete. Summary of the invention
[0008] In view of the shortcomings of the prior art, the first aspect of the present invention is to provide a new type of high water-resistant cement penetrating crystallization mortar, which is prepared by using the following materials: by weight: 35-40 parts of cement, 15-22 parts of tap water, 100-130 parts of fine aggregate, and 0.15-1 part of cement-based penetrating crystallization waterproof additive, wherein the cement-based penetrating crystallization waterproof additive is Ca 54 MgAl2Si 16 O 90 , C3S and gypsum, preferably the addition amount of the cement-based penetrating crystalline waterproof additive is 1%-1.5% of the cement mass.
[0009] Furthermore, the mass percentages of the oxides in the chemical composition of the cement-based penetrating crystalline waterproofing agent are: CaO-51.43%; SiO2-14.92%; Na2O-8.45%; Al2O3-4.16%; MgO-2.23%; Fe2O3-1.90%; K2O-0.67%; TiO2-0.16%; SrO-0.16%; and others 15.92%.
[0010] Furthermore, the water-cement ratio is 0.45-0.55, preferably 0.45-0.5.
[0011] Further, the cement has a density of 3000-3200 kg / m 3 PO42.5 ordinary Portland cement.
[0012] Furthermore, the cement may be PO42.5 ordinary Portland cement having a density of 3112 kg / m³.
[0013] Furthermore, the fine aggregate is river sand with a maximum particle size not exceeding 5 mm, and the apparent density of the river sand is 2654 kg / m 3 , the water absorption rate is 0.36%.
[0014] Furthermore, the water can be tap water from a city water supply plant.
[0015] In a second aspect, the present invention further discloses a method for preparing a novel high water-resistant cement penetration crystallization mortar, comprising the following steps: (1) Weigh 35-40 parts of cement, 15-22 parts of tap water, 100-130 parts of fine aggregate, and 0.15-1 part of cement-based penetrating crystalline waterproof additive according to the mass ratio; (2) Mix and stir the weighed water and cement, and then add the cement-based penetrating crystalline waterproofing agent into the two materials to obtain a mixed material; (3) After the mixture obtained in step (2) is stirred at a low speed for 30 seconds ± 1 second, fine aggregate is evenly added at the beginning of the second 30 seconds ± 1 second, and the mixer is adjusted to a high speed and stirring is continued for 2-3 minutes; (4) Stop stirring and let it stand for 90-120 seconds. Within 15 seconds ± 1 second after stopping stirring, scrape the remaining mortar in the stirrer into the pot, and continue stirring at high speed for 60 seconds ± 1 second until the mixture is uniform; (5) Pour the mixture obtained in step (4) evenly into the mold, and place the mold on a vibration table for vibration; (6) The test piece of step (5) is demolded and placed in a constant temperature and humidity environment for curing.
[0016] Furthermore, the low-speed stirring speed is 40-60 r / min; the high-speed stirring speed is 80-100 r / min.
[0017] Furthermore, the mixing and stirring in step (2) is carried out using a vertical mixer, wherein the rotation speed of the stirring blade is 80±2 r / min and the rotation speed of the stirring drum is 60±2 r / min.
[0018] Furthermore, the mold in step (5) is a triple mold, and during the vibration process, material is continuously added to the mold until the mold is full and no steam bubble emerges.
[0019] Furthermore, the novel high water-resistant cement penetration crystallization mortar has a compressive strength of 52-56 MPa and a flexural strength of 13.5-14 MPa.
[0020] Furthermore, the added amount of the cement-based penetrating crystalline waterproof additive is 1.2%-1.5% of the cement mass.
[0021] In a third aspect, the present application seeks protection for a waterproof building material prepared using the mortar described in the first aspect.
[0022] Beneficial effects of the present invention: (1) The present invention provides a novel high water-resistant cement penetrating crystallization mortar having excellent flexural resistance, compressive resistance and impermeability.
[0023] (2) The novel high water-resistant cement permeable crystallization mortar provided by the present invention has good flexural properties. For specimens with water-cement ratios of 0.45, 0.50, and 0.55, when the amount of CCCW material added increases from 0% to 2.5%, the flexural strength of the specimens first increases and then decreases with the increase in the amount of CCCW. Among them, when the amount of CCCW is 1.5%, the flexural strength of the specimen is the largest, which is 14.10MPa, 13.5MPa, and 12.20MPa, respectively.
[0024] (3) The novel high water-resistant cement permeable crystallization mortar provided by the present invention has good compressive properties. For specimens with water-cement ratios of 0.45, 0.50, and 0.55, as the CCCW content increases from 0% to 2.5%, the compressive strength of the specimens first increases and then decreases. When the CCCW content is 1.5%, the compressive strength of the mortar specimens is 57.4 MPa, 52.2 MPa, and 47.3 MPa, respectively.
[0025] (4) The novel high water-resistant cement permeable crystallization mortar provided by the present invention has good anti-seepage performance. For the specimens with water-cement ratios of 0.45, 0.50, and 0.55, as the CCCW content increases from 0% to 2.5%, the anti-seepage strength of the specimens first increases and then decreases. When the CCCW content is 1.5%, the anti-seepage heights of the mortar specimens are 5.35 cm, 5.68 cm, and 6.32 cm, respectively.
[0026] (5) The present invention adopts Ca as the main crystal phase 54 MgAl2Si 16 O 90 , C3S and gypsum, an inorganic rigid waterproof material, was used to obtain a mortar with good compressive strength, flexural strength and impermeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will be further described below in conjunction with the accompanying drawings.
[0028] Figure 1 This is a flow chart for preparing the novel high water-resistant cement penetration crystallization mortar of the present invention.
[0029] Figure 2 This is a graph showing the flexural strength test results of the novel high water-resistant cement penetration crystallization mortar of the present invention.
[0030] Figure 3 This is a graph showing the compressive strength test results of the novel high water-resistant cement penetration crystallization mortar of the present invention.
[0031] Figure 4 This is a graph showing the test results of the anti-seepage height of the novel high water-resistant cement penetration crystallization mortar of the present invention.
[0032] Figure 5 This is a SEM picture of the novel high water-resistant cement penetration crystallization mortar of the present invention. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with examples, but the implementation manner and protection scope of the present invention are not limited to the following examples. Comparative Example 1
[0034] The mortar of this comparative example does not involve the addition of cement-based penetrating crystalline waterproof material (CCCW), and includes the following steps: The formula mass parts are calculated as follows: (1) 3780 g of cement; (2) 1705 g of tap water; (3) 11340 g of fine aggregate.
[0035] The cement is PO42.5 ordinary Portland cement with a density of 3112kg / m³.
[0036] Wherein, the water is tap water from a city water supply plant.
[0037] The fine aggregate is river sand with a maximum particle size not exceeding 5 mm, the apparent density of the river sand is 2654 kg / m³, and the water absorption rate is 0.36%.
[0038] The above materials were tested according to the following steps to obtain a new type of highly water-resistant mortar, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 1705g of tap water, and 11340g of fine aggregate using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0039] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0040] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0041] Since no cement-based penetrating crystalline waterproofing agent was added in Comparative Example 1, it was named SHB0.45P0. Example 1
[0042] The components, weight proportions and testing methods of the novel high water-resistant mortar in this embodiment are the same as those in the blank example, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 18.9 g.
[0043] Among them, the cement-based penetrating crystalline waterproofing agent is selected from the main crystal phase of Ca 54 MgAl2Si 16 O 90 , C3S and gypsum inorganic rigid waterproof material. Preferably, the mass percentage of each oxide in the chemical composition of the cement-based penetrating crystalline waterproofing agent is: CaO (51.43%), SiO2 (14.92%), Na2O (8.45%), Al2O3 (4.16%), MgO (2.23%), Fe2O3 (1.90%), K2O (0.67%), TiO2 (0.16%), SrO (0.16%) and others (15.92%).
[0044] The above materials were tested according to the following steps to obtain a new type of crack-resistant and impermeable concrete, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 1705g of tap water, 11340g of fine aggregate, and 18.9g of cement-based penetrating crystalline waterproofing agent using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0045] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0046] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0047] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 1 accounts for 0.5% of the cement content, it is named SHB0.45P0.5. Example 2
[0048] The components, weight fractions and testing methods of the novel high water-resistant mortar in this embodiment are the same as those in Example 1, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 37.8 g.
[0049] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 2 accounts for 1% of the cement content, it is named SHB0.45P1. Example 3
[0050] The components, weight fractions and testing methods of the novel high water-resistant mortar in this embodiment are the same as those in Example 1, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 56.7 g.
[0051] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 3 accounts for 1.5% of the cement content, it is named SHB0.45P1.5. Example 4
[0052] The components, weight fractions and testing methods of the novel high water-resistant mortar in this embodiment are the same as those in Example 1, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 75.6 g.
[0053] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 4 accounts for 2.0% of the cement content, it is named SHB0.45P2. Example 5
[0054] The components, weight fractions and testing methods of the novel high water-resistant mortar in this embodiment are the same as those in Example 1, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 94.5 g.
[0055] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 5 accounts for 2.5% of the cement content, it is named SHB0.45P2.5. Comparative Example 2
[0056] The new high water-resistant mortar implemented in this invention does not involve cement-based penetrating crystalline waterproof material (CCCW), and includes the following steps: The formula mass parts are calculated as follows: (1) 3780 g of cement; (2) 1890 g of tap water; (3) 11340 g of fine aggregate.
[0057] The cement is PO42.5 ordinary Portland cement with a density of 3112kg / m³.
[0058] Wherein, the water is tap water from a city water supply plant.
[0059] The fine aggregate is river sand with a maximum particle size not exceeding 5 mm. Preferably, the apparent density of the river sand is 2654 kg / m³ and the water absorption rate is 0.36%.
[0060] The above materials were tested according to the following steps to obtain a new type of highly water-resistant mortar, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 1890g of tap water, and 11340g of fine aggregate using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0061] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0062] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0063] Since no cement-based penetrating crystalline waterproofing agent was added in Blank Example 2, it was named SHB0.50P0. Example 6
[0064] The components, weight proportions and testing methods of the novel high water-resistant mortar in this embodiment are the same as those in the blank example, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 18.9 g.
[0065] Among them, the cement-based penetrating crystalline waterproofing agent is selected from the main crystal phase of Ca 54 MgAl2Si 16 O 90 , C3S and gypsum inorganic rigid waterproof material. Preferably, the mass percentage of each oxide in the chemical composition of the cement-based penetrating crystalline waterproofing agent is: CaO (51.43%), SiO2 (14.92%), Na2O (8.45%), Al2O3 (4.16%), MgO (2.23%), Fe2O3 (1.90%), K2O (0.67%), TiO2 (0.16%), SrO (0.16%) and others (15.92%).
[0066] The above materials were tested according to the following steps to obtain a new type of crack-resistant and impermeable concrete. Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 1890g of tap water, 11340g of fine aggregate, and 18.9g of cement-based penetrating crystalline waterproofing agent using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0067] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0068] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0069] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 6 accounts for 0.5% of the cement content, it is named SHB0.5P0.5.
[0070] Example 7: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 6, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 37.8 g.
[0071] Among them, the cement-based penetrating crystalline waterproofing agent is selected from the main crystal phase of Ca 54 MgAl2Si 16 O 90 , C3S and gypsum inorganic rigid waterproof material. Preferably, the mass percentage of each oxide in the chemical composition of the cement-based penetrating crystalline waterproofing agent is: CaO (51.43%), SiO2 (14.92%), Na2O (8.45%), Al2O3 (4.16%), MgO (2.23%), Fe2O3 (1.90%), K2O (0.67%), TiO2 (0.16%), SrO (0.16%) and others (15.92%).
[0072] The above materials were tested according to the following steps to obtain a new type of crack-resistant and impermeable concrete, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 1890g of tap water, 11340g of fine aggregate, and 37.8g of cement-based penetrating crystalline waterproofing agent using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0073] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0074] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0075] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 7 accounts for 1.0% of the cement content, it is named SHB0.5P1.
[0076] Example 8: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 6, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 56.7 g.
[0077] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 8 accounts for 1.5% of the cement content, it is named SHB0.5P1.5.
[0078] Example 9: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 6, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 75.6 g.
[0079] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 9 accounts for 2.0% of the cement content, it is named SHB0.5P2.
[0080] Example 10: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 6, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 94.5 g.
[0081] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 10 accounts for 2.5% of the cement content, it is named SHB0.5P2.5.
[0082] Comparative Example 3: The novel high water-resistant mortar of this embodiment does not involve cement-based penetrating crystalline waterproof material (CCCW), and includes the following steps: The formula mass parts are calculated as follows: (1) 3780 g of cement; (2) 2080 g of tap water; (3) 11340 g of fine aggregate.
[0083] The cement is PO42.5 ordinary Portland cement with a density of 3112kg / m³.
[0084] Wherein, the water is tap water from a city water supply plant.
[0085] The fine aggregate is river sand with a maximum particle size not exceeding 5 mm. Preferably, the apparent density of the river sand is 2654 kg / m³ and the water absorption rate is 0.36%.
[0086] The above materials were tested according to the following steps to obtain a new type of highly water-resistant mortar, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 2080g of tap water, and 11340g of fine aggregate using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0087] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0088] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0089] Since no cement-based penetrating crystalline waterproofing agent was added in Blank Example 3, it was named SHB0.55P0.
[0090] Example 11: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Blank Example 3, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 18.9 g.
[0091] Among them, the cement-based penetrating crystalline waterproofing agent is selected from the main crystal phase of Ca 54 MgAl2Si 16 O 90 , C3S and gypsum inorganic rigid waterproof material. Preferably, the mass percentage of each oxide in the chemical composition of the cement-based penetrating crystalline waterproofing agent is: CaO (51.43%), SiO2 (14.92%), Na2O (8.45%), Al2O3 (4.16%), MgO (2.23%), Fe2O3 (1.90%), K2O (0.67%), TiO2 (0.16%), SrO (0.16%) and others (15.92%).
[0092] The above materials were tested according to the following steps to obtain a new type of crack-resistant and impermeable concrete, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 2080g of tap water, 11340g of fine aggregate, and 18.9g of cement-based penetrating crystalline waterproofing agent using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0093] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0094] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0095] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 11 accounts for 0.5% of the cement content, it is named SHB0.6P0.5.
[0096] Example 12: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 11, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 37.8 g.
[0097] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 12 accounts for 1.0% of the cement content, it is named SHB0.6P1.
[0098] Example 13: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 11, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 56.7 g.
[0099] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 13 accounts for 1.5% of the cement content, it is named SHB0.6P1.5.
[0100] Example 14: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in the blank example, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 75.6 g.
[0101] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 14 accounts for 2.0% of the cement content, it is named SHB0.6P2.
[0102] Example 15: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 11, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 94.5 g.
[0103] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 15 accounts for 2.5% of the cement content, it is named SHB0.6P2.5. Impermeability test
[0104] Comparative Example 4: The novel high water-resistant mortar of this embodiment does not involve cement-based penetrating crystalline waterproof material (CCCW), and includes the following steps: The formula mass parts are calculated as follows: (1) 3780 g of cement; (2) 1705 g of tap water; (3) 11340 g of fine aggregate.
[0105] The cement is PO42.5 ordinary Portland cement with a density of 3112kg / m³.
[0106] Wherein, the water is tap water from a city water supply plant.
[0107] The fine aggregate is river sand with a maximum particle size not exceeding 5 mm. Preferably, the apparent density of the river sand is 2654 kg / m³ and the water absorption rate is 0.36%.
[0108] The above materials were tested according to the following steps to obtain a new type of highly water-resistant mortar, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 1705g of tap water, and 11340g of fine aggregate using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the truncated cone mold brushed with engine oil, and place the truncated cone mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0109] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0110] (7) The samples cured in step (6) are subjected to a permeability test using a mortar permeability tester. The permeability test is performed on three test pieces to obtain an average value.
[0111] Since no cement-based penetrating crystalline waterproofing agent was added in Blank Example 4, it was named SHB0.45P0.
[0112] Example 16: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Blank Example 4, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 18.9 g.
[0113] Among them, the cement-based penetrating crystalline waterproofing agent is selected from the main crystal phase of Ca 54 MgAl2Si 16 O 90 , C3S and gypsum inorganic rigid waterproof material. Preferably, the mass percentage of each oxide in the chemical composition of the cement-based penetrating crystalline waterproofing agent is: CaO (51.43%), SiO2 (14.92%), Na2O (8.45%), Al2O3 (4.16%), MgO (2.23%), Fe2O3 (1.90%), K2O (0.67%), TiO2 (0.16%), SrO (0.16%) and others (15.92%).
[0114] The above materials were tested according to the following steps to obtain a new type of crack-resistant and impermeable concrete, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 1705g of tap water, 11340g of fine aggregate, and 18.9g of cement-based penetrating crystalline waterproofing agent using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0115] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0116] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0117] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 16 accounts for 0.5% of the cement content, it is named SHB0.45P0.5.
[0118] Example 17: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 16, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 37.8 g.
[0119] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 17 accounts for 1% of the cement content, it is named SHB0.45P1.
[0120] Example 18: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 16, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 56.7 g.
[0121] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 18 accounts for 1.5% of the cement content, it is named SHB0.45P1.5.
[0122] Example 19: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 16, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 75.6 g.
[0123] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 19 accounts for 2.0% of the cement content, it is named SHB0.45P2.
[0124] Example 20: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 16, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 94.5 g.
[0125] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 20 accounts for 2.5% of the cement content, it is named SHB0.45P2.5.
[0126] Comparative Example 5: The novel high water-resistant mortar of this embodiment does not involve cement-based penetrating crystalline waterproof material (CCCW), and includes the following steps: The formula mass parts are calculated as follows: (1) 3780 g of cement; (2) 1890 g of tap water; (3) 11340 g of fine aggregate.
[0127] The cement is PO42.5 ordinary Portland cement with a density of 3112kg / m³.
[0128] Wherein, the water is tap water from a city water supply plant.
[0129] The fine aggregate is river sand with a maximum particle size not exceeding 5 mm. Preferably, the apparent density of the river sand is 2654 kg / m³ and the water absorption rate is 0.36%.
[0130] The above materials were tested according to the following steps to obtain a new type of highly water-resistant mortar, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 1890g of tap water, and 11340g of fine aggregate using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the truncated cone mold brushed with engine oil, and place the truncated cone mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0131] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0132] (7) The samples cured in step (6) are subjected to a permeability test using a mortar permeability tester. The permeability test is performed on three test pieces to obtain an average value.
[0133] Since no cement-based penetrating crystalline waterproofing agent was added in Blank Example 5, it was named SHB0.50P0.
[0134] Example 21: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Blank Example 5, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 18.9 g.
[0135] Among them, the cement-based penetrating crystalline waterproofing agent is selected from the main crystal phase of Ca 54 MgAl2Si 16 O 90 , C3S and gypsum inorganic rigid waterproof material. Preferably, the mass percentage of each oxide in the chemical composition of the cement-based penetrating crystalline waterproofing agent is: CaO (51.43%), SiO2 (14.92%), Na2O (8.45%), Al2O3 (4.16%), MgO (2.23%), Fe2O3 (1.90%), K2O (0.67%), TiO2 (0.16%), SrO (0.16%) and others (15.92%).
[0136] The above materials were tested according to the following steps to obtain a new type of crack-resistant and impermeable concrete. Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 1890g of tap water, 11340g of fine aggregate, and 18.9g of cement-based penetrating crystalline waterproofing agent using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0137] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0138] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0139] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 21 accounts for 0.5% of the cement content, it is named SHB0.5P0.5.
[0140] Example 22: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 21, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 37.8 g.
[0141] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 22 accounts for 1.0% of the cement content, it is named SHB0.5P1.
[0142] Example 23: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 21, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 56.7 g.
[0143] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 23 accounts for 1.5% of the cement content, it is named SHB0.5P1.5.
[0144] Example 24: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 21, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 75.6 g.
[0145] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 24 accounts for 2.0% of the cement content, it is named SHB0.5P2.
[0146] Example 25: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 21, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 94.5 g.
[0147] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 25 accounts for 2.5% of the cement content, it is named SHB0.5P2.5.
[0148] Comparative Example 6: The novel high water-resistant mortar of this embodiment does not involve cement-based penetrating crystalline waterproof material (CCCW), and includes the following steps: The formula mass parts are calculated as follows: (1) 3780 g of cement; (2) 2080 g of tap water; (3) 11340 g of fine aggregate.
[0149] The cement is PO42.5 ordinary Portland cement with a density of 3112kg / m³.
[0150] Wherein, the water is tap water from a city water supply plant.
[0151] The fine aggregate is river sand with a maximum particle size not exceeding 5 mm. Preferably, the apparent density of the river sand is 2654 kg / m³ and the water absorption rate is 0.36%.
[0152] The above materials were tested according to the following steps to obtain a new type of highly water-resistant mortar, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 2080g of tap water, and 11340g of fine aggregate using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the truncated cone mold brushed with engine oil, and place the truncated cone mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0153] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0154] (7) The samples cured in step (6) are subjected to a permeability test using a mortar permeability tester. The permeability test is performed on three test pieces to obtain an average value.
[0155] Since no cement-based penetrating crystalline waterproofing agent was added in Blank Example 6, it was named SHB0.55P0.
[0156] Example 26: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Blank Example 6, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 18.9 g.
[0157] Among them, the cement-based penetrating crystalline waterproofing agent is selected from the main crystal phase of Ca 54 MgAl2Si 16 O 90, C3S and gypsum inorganic rigid waterproof material. Preferably, the mass percentage of each oxide in the chemical composition of the cement-based penetrating crystalline waterproofing agent is: CaO (51.43%), SiO2 (14.92%), Na2O (8.45%), Al2O3 (4.16%), MgO (2.23%), Fe2O3 (1.90%), K2O (0.67%), TiO2 (0.16%), SrO (0.16%) and others (15.92%).
[0158] The above materials were tested according to the following steps to obtain a new type of crack-resistant and impermeable concrete, such as Figure 1 As shown, the following steps are included: (1) Weigh 3780g of cement, 2080g of tap water, 11340g of fine aggregate, and 18.9g of cement-based penetrating crystalline waterproofing agent using a scientific electronic balance; (2) Mix the weighed water and ordinary Portland cement and put them into a 28L vertical mixer. Stir evenly for 2-3 minutes at a speed of 80±2r / min for the stirring blade and 60±2r / min for the mixing drum to obtain a uniform mixture. (3) Slowly pour the weighed fine aggregate into a 28L vertical mixer, stir evenly for 2-3 minutes at a stirring blade speed of 80±2r / min and a mixing drum speed of 60±2r / min to obtain a uniform mortar mixture; (4) Pour the mortar mixture stirred in step (3) into 2 / 3 of the triple mold that has been brushed with engine oil, and place the triple mold on a vibrating table for vibration. During the vibration process, continuously add material to the mold until the mold is full and no steam bubble comes out; (5) Place the mortar mold vibrated in step (4) on a relatively flat surface and smooth and polish the surface of the mold with a plastering scraper. To avoid excessive evaporation of water that may adversely affect the cement hydration reaction rate, the specimen must be sealed and covered with plastic film or wet cloth as soon as possible.
[0159] (6) After the specimens in step (5) are left to cure at room temperature for 24 hours, the mortar specimens are demoulded, the specimen molds are cleaned, and the concrete specimens are then placed in water for curing for 28 days. After the curing period is completed, the specimens can be taken out, dried, and tested.
[0160] (7) The samples cured in step (6) are subjected to flexural and compressive strength tests using a flexural and compressive testing machine. The flexural strength test is performed by taking the average value of three test pieces, and the compressive strength test is performed by taking the average value of six broken test pieces.
[0161] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 26 accounts for 0.5% of the cement content, it is named SHB0.6P0.5.
[0162] Example 27: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 26, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 37.8 g.
[0163] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 27 accounts for 1.0% of the cement content, it is named SHB0.6P1.
[0164] Example 28: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 26, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 56.7 g.
[0165] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 28 accounts for 1.5% of the cement content, it is named SHB0.6P1.5.
[0166] Example 29: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 26, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 75.6 g.
[0167] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 29 accounts for 2.0% of the cement content, it is named SHB0.6P2.
[0168] Example 30: The components, mass parts and testing methods of the new high water-resistant mortar in this example are the same as those in Example 26, except that a cement-based penetrating crystalline waterproofing agent (CCCW) is added as a powder additive, and the amount of CCCW is 94.5 g.
[0169] Since the amount of cement-based penetrating crystalline waterproofing agent added in Example 30 accounts for 2.5% of the cement content, it is named SHB0.6P2.5.
[0170] Conclusion: Figure 2 It can be seen that for the SHB0.45 series, when the CCCW content increases from 0% to 2.5%, the flexural strength of the specimen increases slightly from 13.4MPa to 13.9MPa, and the compressive strength of the specimen increases slightly from 53.00MPa to 55.30MPa.
[0171] For SHB0.45, SHB0.50 and SHB0.55 series, the flexural and compressive strengths first increase and then decrease with the increase of CCCW content. When the CCCW content is 1.5%, the flexural and compressive strengths are the largest, with the flexural strengths being 14.10MPa, 13.50MPa and 12.20MPa, respectively, and the compressive strengths being 57.40MPa, 52.22MPa and 47.27MPa, respectively.
[0172] However, when the CCCW dosage is further added to 2.5%, the flexural and compressive strengths decrease, and the flexural strengths are 13.90MPa, 13.00MPa, and 12.00MPa, respectively, and the compressive strengths are 55.30MPa, 51.75MPa, and 45.28MPa, respectively.
[0173] This is because CCCW is a material containing special active substances, the active substances in which can react with unhydrated substances in concrete to generate many insoluble crystals, fill the micropores and capillary channels of the mortar, and effectively improve the density of the mortar, thereby comprehensively improving the flexural and compressive strengths of the mortar specimens. However, when the CCCW dosage is too high, too many crystals will be generated, making the interior of the mortar too dense, causing the mortar specimens to expand and produce many defects again, resulting in a decrease in the mechanical strength of the mortar. In addition, with the increase of the water-cement ratio, the compressive strength of the mortar with different CCCW dosages shows a gradual downward trend. This may be because as the water-cement ratio increases, the amount of water used increases, the reaction and hydration of cement are more thorough, and the substances in the mortar that can react with the active masterbatch of CCCW are reduced, thereby reducing the amount of crystals generated and the filling effect of internal defects in the concrete becomes worse. According to Figure 2 , 3 The results show that when the content of CCCW is 1.5% of the cement content, the best flexural and compressive properties of this test are achieved.
[0174] The results of the anti-seepage strength test are as follows: Figure 4 As shown. For the SHB0.50 series, the addition of CCCW reduces the water penetration resistance height of the mortar specimens. When the CCCW dosage increases from 0% to 2.5%, the water penetration resistance height of the mortar decreases slightly from 9.25cm to 5.73cm. For the SHB0.45, SHB0.50 and SHB0.55 series, with the increase of CCCW dosage, the water penetration resistance height of the mortar gradually decreases, and the impermeability strength gradually increases. When the CCCW dosage is 2.5%, the water penetration resistance height of the mortar is the lowest, which is 4.20cm, 5.73cm, and 3.13cm, respectively. This may be because the active substances in CCCW can react with the substances in the mortar to generate many insoluble crystals, fill the micropores and capillary channels of the mortar specimens, effectively increase the density of the mortar specimens, and to a certain extent limit the expansion of cracks, thereby improving the impermeability strength of the mortar.
[0175] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A new type of high water-resistant cement penetrating crystallization mortar, characterized by: The novel high water-resistant cement penetrating crystallization mortar is prepared by using the following materials: by weight: 35-40 parts of cement, 15-22 parts of tap water, 100-130 parts of fine aggregate, 0.15-1 part of cement-based penetrating crystallization waterproof additive, wherein the cement-based penetrating crystallization waterproof additive is Ca 54 MgAl2Si 16 O 90 , C3S and gypsum, preferably the addition amount of the cement-based penetrating crystalline waterproof additive is 1%-1.5% of the cement mass.
2. A novel high water-resistant cement penetrating crystallization mortar according to claim 1, characterized in that: The mass percentages of the oxides in the chemical composition of the cement-based penetrating crystalline waterproofing agent are: CaO-51.43%; SiO2-14.92%; Na2O-8.45%; Al2O3-4.16%; MgO-2.23%; Fe2O3-1.90%; K2O-0.67%; TiO2-0.16%; SrO-0.16%; and others 15.92%.
3. The novel high water-resistant cement penetrating crystallization mortar according to claim 1 is characterized in that: The water-cement ratio is 0.45-0.55, preferably 0.45-0.
5.
4. A novel high water-resistant cement penetrating crystallization mortar according to any one of claims 1 to 3, characterized in that: The density of cement is 3000-3200kg / m 3 PO42.5 ordinary Portland cement.
5. A novel high water-resistant cement penetration crystallization mortar according to any one of claims 1 to 3, characterized in that: The fine aggregate is river sand with a maximum particle size not exceeding 5 mm. The apparent density of the river sand is 2654 kg / m³ and the water absorption rate is 0.36%.
6. A method for preparing a novel high water-resistant cement penetration crystallization mortar according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Weigh 35-40 parts of cement, 15-22 parts of tap water, 100-130 parts of fine aggregate, and 0.15-1 part of cement-based penetrating crystalline waterproof additive according to the mass ratio; (2) Mix and stir the weighed water and cement, and then add the cement-based penetrating crystalline waterproofing agent into the two materials to obtain a mixed material; (3) After the mixture obtained in step (2) is stirred at a low speed for 30 seconds ± 1 second, fine aggregate is evenly added at the beginning of the second 30 seconds ± 1 second, and the mixer is adjusted to a high speed and stirring is continued for 2-3 minutes; (4) Stop stirring and let it stand for 90-120 seconds. Within 15 seconds ± 1 second after stopping stirring, scrape the remaining mortar in the stirrer into the pot, and continue stirring at high speed for 60 seconds ± 1 second until the mixture is uniform; (5) Pour the mixture obtained in step (4) evenly into the mold, and place the mold on a vibration table for vibration; (6) The test piece of step (5) is demolded and placed in a constant temperature and humidity environment for curing.
7. The method for preparing a novel high water-resistant cement penetration crystallization mortar according to claim 6, characterized in that: The low-speed stirring speed is 40-60 r / min; the high-speed stirring speed is 80-100 r / min; the mixing and stirring in step (2) adopts a vertical mixer, wherein the stirring blade speed is 80±2 r / min, and the stirring drum speed is 60±2 r / min; the mold in step (5) is a triple mold, and during the vibration process, the material is continuously added to the mold until the mold is full and no steam bubble emerges.
8. The method for preparing a novel high water-resistant cement penetration crystallization mortar according to claim 6, characterized in that: The novel high water-resistant cement penetration crystallization mortar has a compressive strength of 52.2-56 MPa and a flexural strength of 13-14 MPa.
9. The method for preparing a novel high water-resistant cement penetration crystallization mortar according to claim 6, characterized in that: The added amount of the cement-based penetrating crystalline waterproof additive is 1.2%-1.5% of the cement mass.
10. A waterproof building material, characterized in that The mortar is prepared by using a new type of highly water-resistant cement penetration crystallization mortar as described in claims 1-5.
Citation Information
Patent Citations
Cement base permetration crystal type water-proof material and its producing process and construction method
CN1587173A